The Sensitivity of Financial Position and Financial Behavior of Young Workers - Kabul Wahyu Utomo, Mila Arlinawati, Ni Nyoman Sawitri, (Jurnal Manajemen, 2020)
The phenomenon of financial behavior from young workers in Indonesia is important to be studied; it relates to the financial position in the future. Reviewing for the phenomenon, so this research focuses on the impact of financial behavior on financial position supported by financial ability, locus of control, financial knowledge, financial attitude, income, and individual ethnicity. This experimental study is conducted on young workers in Jakarta (Indonesia), it is about 132 young workers taken data through questionnaires. The analysis technique used by path analysis with Smart PLS tools. The research finding is found that financial behavior does not always determine the financial position of young workers. Many other cases can determine financial position directly are financial knowledge and the ethnicity of young workers. While financial behavior can be truly created by the support of financial ability, financial attitude, and income.